Fostering actions for a sustainable future: critical reflections on the ‘ASF hub’ as a case study of experimental and innovative research governance - Leo Hosp; Ariadne Sevgi Avkıran; Dorothea Born (Journal of Responsible Innovation)
The ‘Action for Sustainable Future (ASF) hub’ is introduced as an effort of responsible and innovative research governance for tackling ongoing sustainability crises. From 2021 to 2023, the hub was a cross-institutional structure for projects initiated and conducted by civil actors, combining monetary funding, support in project management, and artistic and experimental facilitation. Through its experimental approach and implementation of Open Innovation in Science principles, the hub aimed to transform prevalent research governance practices. It challenged epistemic hierarchies and capitalist notions of productivity within research, offered space for developing innovative solutions to sustainability issues, and facilitated societal engagement. Yet, required resources like expertise, time, or personnel could not always be found, leading to skepticism, refusal, and overburdening. Policy recommendations thus center proper preparations of such structures: Their implications must be thought through and made transparent.